Mutated DNMT3A creates a public HLADQ- binding neoantigen on acute myeloid leukemia - van der Lee, Dyantha I.; Argiro, Eva M.; Laan, Sebastiaan N. J.; Honders, M. Willy; de Jong, Rob C. M.; Struckman, Nadine E.; Falkenburg, J. H. Frederik; Griffioen, Marieke (Frontiers in Immunology, 2025)
IntroductionPatients with acute myeloid leukemia (AML) often carry the same gene mutations. Neoantigens encoded by these mutations are attractive targets for immunotherapy.MethodsWe searched for public human leukocyte antigen (HLA) class II-restricted neoantigens on AML using an in vitro T cell stimulation method. Peptides from 26 recurrent genetic aberrations were assessed for predicted HLA class II binding, and 24 long neopeptides encoded by 10 recurrent mutations were synthesized. Naive CD4 T cells from healthy individuals were cocultured with autologous dendritic cells pulsed with neopeptides.ResultsMultiple CD4 T cell clones were isolated that recognized neopeptides encoded by 5 different genetic aberrations. Two of these peptides, one from the well-known DNMT3A-R882H hotspot mutation and one from a long alternative reading frame created by frameshift mutations in RUNX1, were recognized by CD4 T cell clones after endogenous processing and presentation on cell lines transduced or CRISPR-Cas9-edited with the mutation of interest. The T cell clone for DNMT3A-R882H was also activated upon stimulation with primary AML samples from HLA-DQB1*06:02 or -DQB1*06:03 positive patients with the mutation.ConclusionWe here identified a public HLA class II-restricted neoantigen encoded by a driver mutation occurring in 10% of patients with AML that could become an important target for immunotherapy to treat patients with DNMT3A-R882H-mutated AML.